Cost‐effective porous ceramic tubes fabricated through a phase inversion/casting process using calcined bauxite. Issue 6 (27th June 2018) - Zhu, Zhiwen; Cao, Yanxin; Dong, Xudong; Meng, Xiangeng; Zhao, Yujun; Ding, Zhijie; Wei, Zhaoling
Abstract: Cost‐effective ceramic tubes based on low‐price commercial calcined bauxite for economical separation were fabricated by a new phase‐inversion casting method. The thermal shrinkage and weight loss during heating of the green tubes were characterized by dilatometric analysis and TG, respectively. Three shrinkage stages appear successively, corresponding to the viscous deformation of polymeric binder at 200‐300°C, significant combustion loss of 5.2 wt% at 500‐620°C and sintering shrinkage over 800°C, respectively. However, due to high enough viscosity of the casting suspension that can guarantee the green tube against collapse or deformation during the phase inversion/casting process, the sintered tubes display nearly uniform microstructure instead of characteristic asymmetrical structure of the phase inversion process. The influence of sintering temperature on the pore property (including pore size and porosity) and mechanical strength was investigated. As the sintering temperature increases from 1200 to 1400°C, the porosity and average pore size decrease from 46.4% to 37.0% and from 0.98 to 0.81 μm, respectively, and the flexural strength increases from 25.8 to 65.1 MPa. The cost‐effective ceramic tube sintering at the range of 1250‐1400°C can be capable of functioning as a microfiltration membrane or an ultrafiltration membrane support.